2022
DOI: 10.31219/osf.io/py8ju
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Origin of Immunity by Means of Prior Infection and Vaccination with Implications for the Origin of Species

Abstract: The expectation that vaccines would solve the COVID-19 problem through herd immunity, which followed logical deductions from inflammatory phenomena in which Mechnikov and his contemporaries described immunity as originating from the elimination of pathogens by a system of cells and substances which has since been named the immune system which would prevent onward transmission of the pathogen, has failed to find representation in reality. But upon illustrating the reality in which the immunological phenomena th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Pasteur and his co-workers assumed that the mechanism by which complete immunity is obtained by means of vaccination with pathogens is that which eliminates such pathogens completely when upon illustrating the reality in which immune mechanisms bring about such immunity, I found complete immunity to have its origin in conditions that permit the influence of the pathogen on pathological mechanisms to be completely attenuated so that pathological manifestations are not brought about in response to the pathogen at all irrespective of high the load of such a pathogen may become. 7,8 5. Instead of evidence of the inability of pathogens to spread in an immune organism which Pasteur and co-workers expected on the basis of the logical deduction that the mechanisms that bring about immunity are those that defend the host by destroying pathogens which followed the logical deduction that the mechanism by which pathogens cause diseases is one in which the host is attacked, what they found was the consequence of the new theory of immunity that has emerged from the reality we have illustrated so farthat pathogens must necessarily develop very well in animals that enjoy complete immunity because the influence through which such pathogens cause diseases has been completely attenuated in them.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Pasteur and his co-workers assumed that the mechanism by which complete immunity is obtained by means of vaccination with pathogens is that which eliminates such pathogens completely when upon illustrating the reality in which immune mechanisms bring about such immunity, I found complete immunity to have its origin in conditions that permit the influence of the pathogen on pathological mechanisms to be completely attenuated so that pathological manifestations are not brought about in response to the pathogen at all irrespective of high the load of such a pathogen may become. 7,8 5. Instead of evidence of the inability of pathogens to spread in an immune organism which Pasteur and co-workers expected on the basis of the logical deduction that the mechanisms that bring about immunity are those that defend the host by destroying pathogens which followed the logical deduction that the mechanism by which pathogens cause diseases is one in which the host is attacked, what they found was the consequence of the new theory of immunity that has emerged from the reality we have illustrated so farthat pathogens must necessarily develop very well in animals that enjoy complete immunity because the influence through which such pathogens cause diseases has been completely attenuated in them.…”
mentioning
confidence: 99%
“…1 But the results obtained upon illustrating reality revealed that the evolutionary law is not the biological law by which species appeared on the planet. 8 In this reality, the evolutionary law is that according to which biological entities of different species become similar through convergent changes within a short period of time if they are exposed to the same conditions within such a period. 8 And the illustration of the reality in which the inflammatory responses that bring phagocytosing cells to sites of cell death in animals reveal the trigger of evolution to be mechanisms which do not exist for the good of the species but rather mechanisms which took control of the genetic information in their cells for a selfish purpose which may require them to destroy the organism if necessary.…”
mentioning
confidence: 99%
See 3 more Smart Citations